PENGARUH TEKNOLOGI DALAM PENCIPTAAN KOMPOSISI MUSIK “NOMOPHOBIA” - Hamzaini Hamzaini; Ediwar Ediwar; Elizar Elizar (Institut Seni Indonesia Padang Panjang, 2017)
ABSTRACT Music composition “Nomophobia” is a music inspired by a psychological aberra-tion influenced by someone’s dependency toward gadget or smart-phone in tech-nological development. Nowadays, wherever and whenever the situation is, it will be found many people that are engrossed with their own gadgets. Playing with hand-phone seems to be more fun than having a discussion with other people. As if hand-phone has become the style or the taste that attracts all their awareness. This nomophobia phenomenon is one of the bad impacts given by technological advancement. The magnitude of the lifestyle influence requires people to follow globalization and consume new things related to the advancement and development of today technology, particularly in modern society, there are no more boundaries in socializing, communicating, and so on. Therefore, it emerges a change of behavioral pattern from social behavior to asocial behavior because of that impact. This phenomenon also results on the narrowness of space and time. The differences between real things and illusions have become very thin. As if they live in the real imaginary space. Keywords: Nomophobia, Composition, Social, Asocial, Gadget, Technology